Measuring the Frequency of Inner-Experience Characteristics by Self-Report: The Nevada Inner Experience Questionnaire - Heavey, Christopher L.; Moynihan, Stefanie A.; Brouwers, Vincent P.; Lapping-Carr, Leiszle; Krumm, Alek E.; Kelsey, Jason M.; Turner, Dio K.; Hurlburt, Russell T. (Frontiers in Psychology, 2019)
Descriptive experience sampling has suggested that there are five frequently occurring phenomena of inner experience: inner speaking, inner seeing, unsymbolized thinking, feelings, and sensory awareness. Descriptive experience sampling is a labor- and skill-intensive procedure, so it would be desirable to estimate the frequency of these phenomena by questionnaire. However, appropriate questionnaires either do not exist or have substantial limitations. We therefore created the Nevada Inner Experience Questionnaire (NIEQ), with five subscales estimating the frequency of the each of the frequent phenomena, and examine here its psychometric adequacy. Confirmatory factor analysis validated the five-factor model, and the correlation between an existing self-talk questionnaire (Brinthaupt’s Self-Talk Scale) and the NIEQ inner speaking subscale provides one piece of concurrent validation.